Rapid and objective CT scan prognostic scoring identifies metastatic patients with long-term clinical benefit on anti-PD-1/-L1 therapy. (September 2016) - Dercle, Laurent; Ammari, Samy; Champiat, Stéphane; Massard, Christophe; Ferté, Charles; Taihi, Lokmane; Seban, Romain-David; Aspeslagh, Sandrine; Mahjoubi, Linda; Kamsu-Kom, Nyam; Robert, Caroline; Marabelle, Aurélien; et al.
Abstract: Background: Drugs targeting programmed death receptor-1 (PD-1) and its ligand PD-L1 have shown activity in multiple malignancies. Considering their novel mechanism of action, whether traditional prognostic scores also apply to patients treated with these drugs is unknown. We investigated whether a baseline 3-point (pt) computed tomography (CT) scan (PS3-CT) score and a 7-pt prognostic (PS7) score allowed identifying long-term survivors on anti-PD-1/-L1 therapy. Materials and methods: We reviewed 251 consecutive patients enrolled in phase I trials evaluating anti-PD-1/-L1 agents between 26th December 2011 and 7th September 2015. PS3-CT was calculated using high tumour burden (TB1D-RECIST > 9 cm), low skeletal muscle index (SMI < 53 cm 2 m −2 ) and non-pulmonary visceral metastases (NPVM) (1 pt each). PS7 was calculated by adding lower performance status, decreased serum albumin, increased serum lactate dehydrogenase and more than two distant metastases (1 pt each). Effect on overall survival (OS) of each parameter was tested using Kaplan–Meier and multivariable Cox analyses. Results: PS3-CT was a significant independent predictor of OS (hazard ratio [HR] = 1.39 [95% confidence interval CI = 1.07–1.81], p = 0.01) when compared to the Royal Marsden Hospital, Barbot and American Joint Committee on Cancer scores. High TB (n = 78), low SMI (n = 55) and NPVM (n = 146) were associated with poorer survival (p < 0.01). High TB and low SMI were independent predictors of OS (respective HR of death: 2.00 [95% CI = 1.38–2.88], p < 0.01 and 1.75 [95% CI = 1.15–2.66], p < 0.01). PS7 was a significant predictor of OS (HR = 1.40 [95% CI = 1.25–1.56], p < 0.01). Conclusion: Objective and rapid-risk scoring based on three CT scan parameters allows identifying patients with prolonged OS on anti-PD-1/-L1 therapy, independently from conventional clinical–biological prognostic scores. Highlights: Patients with prolonged OS on anti-PD(L)1 therapy are identified at baseline by rapid and objective prognostic risk scoring. PS3-CT uses quantitative imaging biomarkers: tumour burden (RECIST v1.1), sarcopenia (SMI at L3) and the metastatic site. The single-dimension measure (RECIST v1.1) is strongly correlated with the bi-dimensional measure (used in irRC). PS3-CT is independent from RMH, Barbot and AJCC scores and do not require any additional procedure, time or cost. TB and SMI are strong predictors of OS, specific and independent from clinical-biological biomarkers (PS, LDH and albumin).